PENGARUH METODE HYPNOTIS TERHADAP KEMAMPUAN PESERTA INDIVIDU PADA PELATIHAN HYPNOSTIS PERUSAHAAN MULAWARMAN INSTITUTE PALEMBANG - Arubina Bangsawan; Hendra Musa (Jurnal Apresiasi Ekonomi, 2020)
The purpose of this study is to look at the effect of Hypnosis application on the individual abilities of Corporate Hypnosis Mulawarman Institute Palembang’s training participants. The research design uses pre – experimental designs in the form of one – shot case study and uses paradigm where in this research, there is a group that is given treatment and after a certain amount of time, the result will be observed. The object of the study is comprised of 30 professionals from various different work backgrounds in Palembang and the result proved than there are positive and significant effect of hypnosis application on individual abilities of Corporate Hypnosis Mulawarman Institute Palembang training participants. Overall, it can be concluded that, after studying the application of Corporate Hypnosis, participant can gradually improve their individual work abilities. Although there are still many shortcomings, this method is considered good enough and feasible if used appropriately. Hypnosis application can be used as an alternative solution to improve the ability of individual HR, especially in the cognitive, affective, and physical abilities of individuals in a work context.